2017
DOI: 10.3329/kyamcj.v4i1.32255
|View full text |Cite
|
Sign up to set email alerts
|

Suicide By Hanging: An Analysis Of 312 Cases

Abstract: Hanging, the commonest method of suicide, is a form of violent asphyxia produced by suspending the body with a ligature round the neck. A total of 312 cases of suicidal hanging autopsied in this five years retrospective descriptive study spanning from January 2000 to December 2004 at Sir Salimullah Medical College (SSMC) morgue. The objective of this study was to evaluate the present situation, pattern of hanging, socio-demographic characteristics of victims and probable cause of suicidal hanging of studied po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…This finding agrees with published studies and case reports [1,2,13–20,22–73]. According to a sample of published data summarized in Table 8, full suspension in hanging suicides appears to be more prevalent than partial suspension in eastern cultures [48–64]. Most suicides in the current study, which occurred in North America, were found partially suspended by their neck ligatures, with their feet or knees touching the ground or nearby furniture.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This finding agrees with published studies and case reports [1,2,13–20,22–73]. According to a sample of published data summarized in Table 8, full suspension in hanging suicides appears to be more prevalent than partial suspension in eastern cultures [48–64]. Most suicides in the current study, which occurred in North America, were found partially suspended by their neck ligatures, with their feet or knees touching the ground or nearby furniture.…”
Section: Discussionsupporting
confidence: 91%
“…A relatively consistent detail observed in this study was the tension of neck ligatures in the cases analyzed, which agrees with the forensic literature [22–70]. Knotted homicide strangulation ligatures were typically tighter than suicide ligatures used for hanging.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations